Tidal Characteristics in Southern Waters of Java - Indonesia - Mutaqin, Bachtiar W.; Ningsih, Renny Laksmita (JURNAL GEOGRAFI, 2023)
Detailed information regarding tidal characteristics in Indonesian waters is not yet available evenly, including in the southern waters of Java. Tides are one of the most essential hydro-oceanographic parameters in water dynamics. Therefore, this study aims to analyze the characteristics of the tides in the southern waters of Java, starting from Banten Regency in West Java to Malang Regency in East Java. Tidal data with measurement intervals every one hour were collected from December 23, 2022, to January 20, 2023, from ten tide stations with details: 1 station each in Banten and Central Java, three stations each in West Java and East Java, as well as two stations in Yogyakarta. Data from each station is then processed using the Admiralty method to obtain tidal harmonic constant and Formzahl values. Based on the tidal harmonic constants' amplitude and the Formzahl values (F), the tidal type in the southern waters of Java is a mixed tide prevailing semi-diurnal (F ranged from 0.64 - 1.34). The tidal range in the southern waters of Java ranges from 178 - 332 cm. In more detail, Banten and Pelabuhan Ratu waters are classified as micro tides (the tidal range is 178 and 182 cm, respectively). At the same time, the rest are categorized as meso tides (tide range between 200 - 400 cm).Keywords: Tidal Type, Admiralty, Formzahl, Tidal Range, Indian Ocean